Seroepidemiology and Risk Factors of Toxoplasma gondii Infection among the Newly Enrolled Undergraduates and Postgraduate Students in China - Yang, Na; Wang, Dawei; Xing, Mengen; Li, Chenghuan; Li, Jiaqi; Wu, Anhe; Sang, Xiaoyu; Feng, Ying; Jiang, Ning; Chen, Qijun (Frontiers in Microbiology, 2017)
Toxoplasma gondii is an obligate intracellular zoonotic parasite, infecting warm-blood animals including humans. Previous serological surveys of T. gondii infection have focused on people of different occupations and special groups, such as slaughterhouse workers, AIDS patients and pregnant women. To investigate the potential impact of T. gondii infection on the health of young students, the prevalence of T. gondii infection and associated risk factors among the newly-enrolled undergraduates and postgraduate students were investigated. A total of 3,569 newly-enrolled students (age range: 15-37 years old, median 26 years) from various regions of China were recruited in this study. The serum samples were tested for the presence of T. gondii specific IgG by the modified agglutination test (MAT). Questionnaires were used to collect information on risk factors for T. gondii infection. Sixty-five (1.82%) out of 3,569 participants were seropositive for IgG antibodies to T. gondii by MAT (titer≧1:20). Four variables were found to be positively associated with T. gondii infection, including primary geographical location, living in rural areas, gardening or agriculture, and drinking unboiled water by the univariate logistic regression, and only gardening or agriculture was the independent risk factor for T. gondii positivity by using multivariate logistic regression in this study, which may provide information to guide future research and control policies.